A REVIEW ON SECURITY OF DIGITAL WALLET SYSTEM USING PATTERN RECOGNITION SYSTEM - Saini, Ankush; Sunita, MS. (IJRDO -Journal of Computer Science Engineering, 2017)
A digital wallet refers to an electronic device that allows an individual to make electronic transactions. A client-side digital wallet requires minimal setup & is relatively easy to use. Once software is installed, user begins by entering all pertinent information. To make it convenient for individual dealers to put in two factor authentication by performing as an intermediary, wallets have performed a necessity of gap function. A new customer accepting digital commerce in India on internet primarily would be transacting on an average to a low quality telecommunication networks without a great deal of experience in dealing with online firms or with agents looking at customer services in issues related to payments.